2022
DOI: 10.3892/ijmm.2022.5147
|View full text |Cite
|
Sign up to set email alerts
|

An update on the functional roles of long non‑coding RNAs in ischemic injury (Review)

Abstract: Ischemic injuries result from ischemia and hypoxia in cells. Tissues and organs receive an insufficient supply of nutrients and accumulate metabolic waste, which leads to the development of inflammation, fibrosis and a series of other issues. Ischemic injuries in the brain, heart, kidneys, lungs and other organs can cause severe adverse effects. Acute renal ischemia induces acute renal failure, heart ischemia induces myocardial infarction and cerebral ischemia induces cerebrovascular accidents, leading to loss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 148 publications
0
6
0
Order By: Relevance
“…Moreover, we conducted a literature research and confirmed the functional involvement of above-mentioned upregulated lncRNAs in IS. [ 48 49 50 ] Specially, lncRNA Malat1 was currently a hot research topic for its anti-apoptotic and anti-inflammatory effects in cerebrovasculature to reduce brain ischemic damages. [ 48 51 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, we conducted a literature research and confirmed the functional involvement of above-mentioned upregulated lncRNAs in IS. [ 48 49 50 ] Specially, lncRNA Malat1 was currently a hot research topic for its anti-apoptotic and anti-inflammatory effects in cerebrovasculature to reduce brain ischemic damages. [ 48 51 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 48 49 50 ] Specially, lncRNA Malat1 was currently a hot research topic for its anti-apoptotic and anti-inflammatory effects in cerebrovasculature to reduce brain ischemic damages. [ 48 51 ]…”
Section: Discussionmentioning
confidence: 99%
“…Long non-coding RNA refer to the transcripts of non-coding RNAs that are >200 nucleotides in length, they include five different subtypes: sense lncRNA, antisense lncRNA, bidirectional lncRNA, intergenic lncRNA and intronic lncRNA ( Cao et al, 2022 ). LncRNAs were primarily considered as simply transcriptional by-products, recent research have found that they regulate various physiological and pathophysiological processes, such as immunity, cell differentiation and proliferation ( Zhang and Wang, 2019 ).…”
Section: Downstream Molecules Of N6-methyladenosine Modification In C...mentioning
confidence: 99%
“…If the demands for oxygen are higher than the possible delivery, this leads to hypoxic brain damage, which can further continue to anoxic brain damage if the oxygen delivery is fully disrupted. Throughout life, there are numerous ways that hypoxic/anoxic conditions may occur, and this includes but is not limited to asphyxia [1], cardiac arrest [2], traumatic vascular injuries [3], septic shock [4], drug overdoses [5], carbon monoxide poisoning [6], severe hypotension [7], and brain cerebrovascular diseases such as ischemic stroke [8], as well as other anoxic/hypoxic conditions including obstructive sleep apnea-hypopnea syndrome (OSAHS) [9,10], heart failure [11,12], and acute lung injury [13].…”
Section: Introductionmentioning
confidence: 99%